Acral lentiginous melanoma in an adult patient - Yoandra Seara Govea; Soini González Gámez; Maikel González Pérez (Centro Provincial de Información de Ciencias Médicas, 2016)
The case report of a 58 years white patient is presented with a history of disk herniation in cervical and lumbar regions, who 2 years ago attended the Dermatology Service due to a color change in the fingernail of the third finger of her right hand, symptoms that belonged to a lentigo simplex. In this occasion she presented destruction of the ungueal bed and increase of color which covers the whole fingertip, so another biopsy was carried out and the histological diagnosis of acral lentiginous melanoma (in situ) was confirmed.